Pai Teacher Habituation Strategy In Strengthening Student Character At Man 1 Medan School - Kamil; Yongki Sahuri Nasution; Fadillah Anggraini; Natasya Melizza Azahra; Tasya Feby Indrianti; Irwansyah Putra; Dimas Septiawan Pane (International Journal of Society and Law, 2024)
This study aims to identify the habituation strategy of Islamic Religious Education (PAI) teachers in strengthening the character of students in schools. Qualitative methods are used with data collection techniques through in-depth interviews, participatory observation and document analysis, The data sources in this study are Qur'an Hadith teachers, PAI teachers, Fiqh teachers and MAN 1 Medan students who are the main sources in the data collection process in the field. The results of the study show that effective habituation strategies include: value-based learning, development of moral awareness, strengthening discipline, development of empathy and tolerance and the application of religious principles. This strategy increases moral awareness, forms quality character, improves the ability to deal with conflicts and builds a harmonious relationship between students and teachers. This research contributes to the development of effective and innovative PAI learning strategies.